SISTEM INFORMASI SISKAMLING UNTUK MEWUJUDKAN DESA DIGITAL - Hendrawan, Jodi; Perwitasari, Ika Devi; Ritonga, Ristra Sandra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The process of disseminating information on environmental security or patrol schedules, information about events in the village community as well as information on important situations occurring in Klambir Lima Kebun village, the delivery process of which is carried out by attaching the patrol schedule to security posts or village offices, information dissemination is sometimes still word of mouth. word of mouth and the public often miss the latest environmental information. It would be nice if the conventional method was proposed to design an information system that could be used as a forum for information related to environmental safety that can be accessed anytime and anywhere by the public. A responsive web-based environmental security information system (SISKAMLING) will greatly support the process of accessing information about environmental security in Klambir Lima Kebun village. The web is a means of sharing information digitally. The web is one of the media that really supports human life, especially in today's internet era.